1991
DOI: 10.1126/science.251.4994.655
|View full text |Cite
|
Sign up to set email alerts
|

The Search for Evidence of Large Prehistoric Earthquakes Along the Atlantic Seaboard

Abstract: The spacial distribution of seismically induced liquefaction features discovered along the Atlantic seaboard suggest that during the last 2000 to 5000 years, large earthquakes (body wave magnitude, m(b) >/= 5.8 +/- 0.4) in this region may have been restricted exclusively to South Carolina. Paleoliquefaction evidence for six large prehistoric earthquakes was discovered there. At least five of these past events originated in the Charleston, South Carolina, area, the locale of a magnitude 7+ event in 1886. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Consequently, the paleoliquefaction record is probably most complete for this period (Ref. 334). However, beyond the 2,000-5,000 year range, knowledge of groundwater conditions is considerably less reliable, making gaps in the paleoseismic record much more probable.…”
Section: Sand Blow Explosion Craters or Filled Sand-blow Cratersmentioning
confidence: 99%
“…Consequently, the paleoliquefaction record is probably most complete for this period (Ref. 334). However, beyond the 2,000-5,000 year range, knowledge of groundwater conditions is considerably less reliable, making gaps in the paleoseismic record much more probable.…”
Section: Sand Blow Explosion Craters or Filled Sand-blow Cratersmentioning
confidence: 99%
“…A characteristic rupture model of moment magnitude 7.3 earthquakes, based on the estimated magnitude of the 1886 event (Johnston, 1996b) was assumed. For the M7.3 events a recurrence time of 650 years was used, based on dates of paleoliquefaction events (Amick and Gelinas, 1991;Obermeier et al, 1990, Johnston andSchweig, written comm., 1996).…”
Section: Special Zonesmentioning
confidence: 99%
“…1A) was estimated to have had a modified Mercalli intensity of X (Dutton, 1889;Bollinger, 1977), a magnitude of about 7 (Bollinger, 1977), and a moment magnitude of 7.3 (Johnston, 1996) and signifies a nearby major seismogenic zone beneath this passive margin. Numerous sand blows were associated with this earthquake (Dutton, 1889), and subsequent work on paleo-sand blows (e.g., Amick and Gelinas, 1991;Obermeier et al, 1990) demonstrated that the seismic zone near Charleston (Tarr, 1977;Talwani, 1982;Tarr and Rhea, 1983;Madabhushi and Talwani, 1993) has repeatedly undergone strong earthquakes during late Quaternary time. However, because no fault scarp was observed and the sand blows occurred over a large area (Dutton, 1889), the fault that generated the 1886 earthquake is unknown.…”
Section: Introductionmentioning
confidence: 97%